2023
DOI: 10.1002/hbm.26293
|View full text |Cite
|
Sign up to set email alerts
|

The effect of background liked music on acute pain perception and its neural correlates

Abstract: Music shows tremendous promise in pain relief, especially when considering its nonpharmacological nature. However, our understanding of the precise mechanisms behind music-induced analgesia (MIA) remains poor. The positive emotional state induced by music is one of the key components explaining MIA. To test this possibility and reveal its neural correlates, the present study applied nociceptive laser stimuli to 28 healthy participants when their liked or disliked songs were played as background music, or when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
(80 reference statements)
1
10
0
Order By: Relevance
“…Consistent with our findings, a recent study on real life acute pain showed that personal choice over music (cognitive agency) is a strong predictor for successful music-induced analgesia [59]. Reinforcing these findings, another recent study showed that listening to liked music during acute pain significantly lowered pain ratings compared to disliked music or no music and PLOS ONE decreased brain activity in pain-related areas compared to disliked music [60], In our study, participants did not choose the songs themselves, but it would be natural to assume that highly preferred songs would have been selected had participants had the choice. Moreover, our findings indicate that tapping to music was perceived as more pleasant than merely listening to music, suggesting that it was more rewarding to tap to the music, also consistent with a stronger EOS activation.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, a recent study on real life acute pain showed that personal choice over music (cognitive agency) is a strong predictor for successful music-induced analgesia [59]. Reinforcing these findings, another recent study showed that listening to liked music during acute pain significantly lowered pain ratings compared to disliked music or no music and PLOS ONE decreased brain activity in pain-related areas compared to disliked music [60], In our study, participants did not choose the songs themselves, but it would be natural to assume that highly preferred songs would have been selected had participants had the choice. Moreover, our findings indicate that tapping to music was perceived as more pleasant than merely listening to music, suggesting that it was more rewarding to tap to the music, also consistent with a stronger EOS activation.…”
Section: Discussionsupporting
confidence: 91%
“…Environmental quality is increasingly valued, with the sensory environment of the ward being a key component of patient comfort. Positive environmental modi cations, like art and music, can reduce anxiety, shorten hospital stays, and improve sleep quality 37 , while reducing stressors such as light and noise 19 . The KCT-ERAS program tailors environmental adjustments to enhance physical comfort and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have argued that the therapeutic effects of music are not merely due to distraction (Roy et al, 2008;Lu et al, 2019Lu et al, , 2023. Furthermore, music still reduces outcome measurements of pain even when the music is delivered during general anesthesia and therefore cannot be attributed to distractive influence (Nilsson et al, 2003;Simcock et al, 2008;Hole et al, 2015;Kühlmann et al, 2018).…”
Section: Spinal Cord and Brainstemmentioning
confidence: 99%
“…when listening to music: the type of music that is presented, when and for what period(s) of time, whether it is live or pre-recorded, and the presence or absence of lyrics (e.g., Sakamoto et al, 2018;Martin-Saavedra et al, 2018b;Richard-Lalonde et al, 2020;Wu et al, 2021;Loewy, 2022;Chow et al, 2023;Lee et al, 2023). When listening to favorite music chosen by a patient, pleasant and relaxing choices are often shown to be the most effective (Nilsson et al, 2005;Nilsson, 2008;Roy et al, 2008;Dobek et al, 2014;Hsieh et al, 2014;Garza-Villareal et al, 2017;Lin et al, 2019;Lunde et al, 2019;Antioch et al, 2020;Howlin and Rooney, 2021;Howlin et al, 2022;Colebaugh et al, 2023;Lu et al, 2023;Valevicius et al, 2023). iii.…”
Section: Introduction "One Good Thing About Music When It Hits You Yo...mentioning
confidence: 99%